Pertanggungjawaban Perdata Direksi atas Peredaran Bahan Bakar Minyak RON 90 sebagai RON 92: Tinjauan Hukum Ekonomi Syariah - Harahap, Firda Ramadani; Rokan, Mustapa Khamal (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2025)
This study examines the civil liability of company directors for the distribution of RON 90 fuel packaged and sold as RON 92. This practice causes losses to consumers because the quality of the goods does not match the information provided. The research method employed is normative juridical with statutory and conceptual approaches, supplemented by empirical data from the Indonesian Consumers Foundation (YLKI), the Jakarta Legal Aid Institute (LBH Jakarta), and Celios analysis, which estimates consumer losses at IDR 17.4 trillion per year. The results show that directors can be held civilly liable due to elements of breach of contract and/or unlawful acts resulting from negligence in supervising and controlling the quality of marketed fuel. In Islamic commercial jurisprudence (fiqh muamalah), such actions violate the principles of a valid sales contract because of discrepancies between the goods and the promised specifications. This responsibility also includes the obligation to prevent harm (dharar) to consumers. Therefore, the liability of directors is relevant not only in positive law but also carries strong moral and shar‘i dimensions. This study emphasizes the importance of strengthening fuel quality control and applying Sharia values in state-owned enterprise governance.